Implications of the Contradiction in the Definition of Children Between the Child Protection Law and the Human Rights Law in the Juvenile Justice Process - Fenny Haslizarni; Fenty U. Puluhulawa; Suwitno Y. Imran (International Journal of Law, Crime and Justice, 2025)
This research aims to analyze the differences in the definition of a child's age in the Child Protection Law and the Human Rights Law and how this affects the handling of juvenile cases, as well as the implications of the contradiction in the definition of a child's age between the Child Protection Law and the Human Rights Law in juvenile justice processes. This type of research is normative research. The research results indicate that (1) The difference in the definition of a child in the Child Protection Law (Law No. 35 of 2014) and the Human Rights Law (Law No. 39 of 1999) creates inconsistency in legal protection for children. A fair legal system should provide more protection to vulnerable groups, such as children, without distinguishing their marital status. The principle of justice as fairness requires that every individual, especially vulnerable groups, should receive equal opportunities and maximum protection under the law. However, the definition in the Human Rights Law, which excludes married children, creates injustice and contradicts the principle of non-discrimination outlined in the Convention on the Rights of the Child (CRC). (2) The implication of the contradiction in the definition of a child's age between the Child Protection Law and the Human Rights Law in juvenile justice processes is the legal impact, leading to inconsistency in law enforcement by law enforcement officials. Legal theory highlights that the success of law enforcement is influenced by the alignment between the law, law enforcement officials, and society. In this case, the misalignment of legal definitions complicates the decision-making process for law enforcers in determining the status of a married child, which impacts the protection of their rights. Additionally, the theory of distributive justice emphasizes that the distribution of legal treatment should be proportional to the individual's needs. A married child still requires legal protection as a vulnerable age group, so the legal treatment should reflect this need